The impact of the entrepreneurial environment on Vietnamese tourism students' entrepreneurial intention - Tanam Nguyen; Yang Liub (Global Business & Finance Review (GBFR), 2024)
Purpose: Based on Social and Contextual cognitive theory, this study examines the impact of the entrepreneurial environment on the entrepreneurial intentions of students majoring in tourism in Vietnam. Design/methodology/approach: To standardize the conceptual framework of the study, the author began to use the qualitative research method to build hypotheses, then used the quantitative research method to conduct evaluation and assessment, and calculated the sample of the study with the SPSS software version 25. The study was conducted in the form of online survey research on the sample of 275 undergraduate students of tourism and hospitality management in 7 universities in Vietnam. Findings: The findings show that all six hypotheses of the study are accepted, and they have a positive impact on Vietnamese tourism students' entrepreneurial intention. Among them, the political environment is the most influential. Research limitations/implications: Despite efforts to standardize the conceptual framework, the complexity of the entrepreneurial environment may have led to incomplete consideration of relevant variables. The study primarily examined the impact of the entrepreneurial environment on intentions, not behaviors or outcomes, leaving room for future research to conduct a more comprehensive examination of the entrepreneurial process. These limitations offer opportunities for future research to enhance understanding of the intricate relationship between the entrepreneurial environment and intentions among tourism students in Vietnam. Originality/value: The research contributes to the understanding of entrepreneurial intentions among Vietnamese tourism students and provides practical insights for educators, policymakers, and industry stakeholders. Its focus on the entrepreneurial environment and application of relevant theoretical frameworks position it as a meaningful contribution to the fields of entrepreneurship and tourism education.
Keywords: 650; entrepreneurial environment; entrepreneurial intention; Vietnamese tourism students